MEMBANGUN RASA TOLERANSI PADA KAWASAN GLODOK MELALUI GROUND ZERO ORION PLAZA - Clement Clement; Agnatasya Listianti Mustaram (Jurusan Arsitektur dan Perencanaan, 2022)
Tolerance is a form of mutual respect between human differences from all aspects such as ethnicity, religion, and race. Tolerance will grow by respecting each other and being able to accept differences. The Ground Zero Orion Plaza project is a re-design project of Plaza Orion as a public space with the aim of being a forum for tolerance from heterogeneous communities in the Glodok-Pancoran area which is known as the Chinatown center in Jakarta. Seeing from the historical and cultural aspects, it can be traced that there have been several disputes that contain elements of intolerance in this area, causing degradation in terms of the quality of space to humans in the form of physical, mental, and social degradation. Until now, Orion Plaza and its surroundings have become protected areas every time there is an action movement from the community for fear that what has happened in the past will happen again. This Ground Zero Orion Plaza project is a project that tries to design a space with a neutral concept that can be a place of tolerance and social interaction between equal groups of people so that they have a vision to be a protector of the region from things that smell of intolerance in the present and in the future. Building a space that can foster a sense of tolerance requires a public space that can be used by anyone from any background so that by designing a community and cultural space it can become the result in this design. Keywords: Degradation; Neutral; Public area; Social interactions; Tolerance Abstrak Toleransi merupakan sebuah wujud sikap yang saling menghormati antar perbedaan manusia dari segala aspek seperti suku,agama,dan ras . Rasa toleransi akan tumbuh dengan cara saling menghormati satu sama lain dan mampu menerima perbedaan. Proyek Ground Zero Orion Plaza merupakan sebuah proyek re-desain dari Plaza orion sebagai ruang publik dengan tujuan dapat menjadi wadah toleransi dari masyarakat yang heterogen pada kawasan Glodok-Pancoran yang dikenal sebagai pusat pecinan di Jakarta. Melihat dari aspek Sejarah serta budaya dapat ditelusuri pernah terjadinya beberapa persitiwa perselisihan yang mengandung unsur intoleransi pada daerah ini sehingga menimbulkan adanya degradasi dari segi kualitas ruang hinga manusia dalam bentuk degradasi fisik, mental, dan sosial. Hingga saat ini Plaza orion dan sekitar menjadi kawasan yang dilindungi setiap adanya sebuah gerakan aksi dari masyarakat dengan alasan takut hal yang dahulu pernah terjadi dapat terulang lagi. Projek Ground Zero Orion Plaza ini merupakan proyek yang bertujuan membentuk sebuah ruang yang berkonsep netral yang dapat menjadi wadah toleransi dan interaksi sosial dari antar kalangan masyarakat yang setara sehingga mempunyai visi dapat menjadi pelindung kawasan dari hal yang berbau intoleransi di masa kini dan yang akan datang. Membangun sebuah ruang yang dapat menumbuhkan rasa toleransi dibutuhkan sebuah ruang publik yang dapat digunakan oleh siapa pun dari latar belakang manapun sehingga dengan merancang sebuah ruang untuk komunitas dan budaya dapat menjadi hasil pada peracangan ini.